In‐Situ Spin Labeling of His‐Tagged Proteins: Distance Measurements under In‐Cell Conditions. Issue 41 (26th August 2013) - Baldauf, Christoph; Schulze, Katrin; Lueders, Petra; Bordignon, Enrica; Tampé, Robert
Abstract New spin labeling strategies have immense potential in studying protein structure and dynamics under physiological conditions with electron paramagnetic resonance (EPR) spectroscopy. Here, a new spin‐labeled chemical recognition unit for switchable and concomitantly high affinity binding to His‐tagged proteins was synthesized. In combination with an orthogonal site‐directed spin label, this novel spin probe, Proxyl‐trisNTA (P‐trisNTA) allows the extraction of structural constraints within proteins and macromolecular complexes by EPR. By using the multisubunit maltose import system of E. coli: 1) the topology of the substrate‐binding protein, 2) its substrate‐dependent conformational change, and 3) the formation of the membrane multiprotein complex can be extracted. Notably, the same distance information was retrieved both in vitro and in situ allowing for site‐specific spin labeling in cell lysates under in‐cell conditions. This approach will open new avenues towards in‐cell EPR.